PENGGUNAAN ALAT PERAGA SEDERHANA UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR IPA KELAS VIII SMP NEGERI 8 PAGAR ALAM - Senti Juliyesi (UNIB Press, 2021)
This study aims to describe the use of simple teaching aids to increase the attention and learning achievement of science class VIII at SMP Negeri 8 Pagar Alam. The design of this study used classroom action research based on Kurt Lewin's model. The subjects of this study were students of class VIII.B SMP Negeri 8 Pagar Alam even semester of the 2020/2021 school year. Data collection techniques using observation sheets and tests. Meanwhile, the data analysis technique used the average (mean) and t-test. The results showed that the use of simple teaching aids can increase the attention and achievement of learning science class VIII at SMP Negeri 8 Pagar Alam. The implication of the results of this study is that if teachers want to increase the attention and learning achievement of students in science subjects, simple teaching aids can be used.